La réforme des curriculums par compétences au Bénin - Basile Agbodjogbé; Chantal Amade-Escot; Kossivi Attiklèmè
Ten years after the implementation of the curriculum reform in the Benin secondary educational system, this study looks at the discourses held by different actors (supervisors, mentors, teachers) engaged in the conception, the experiment and the following of the reform in physical education (EPS) and science education (SVT). Semi-formal interviews were conducted with 32 individuals. The content analysis of their discourses was conducted through the ALCESTE software. The findings point out four classes of discourses, each of them related to different viewpoints. The structure of these viewpoints is built around two elements: the statute of the individual within the Benin educational system, the specificity of subject matter discipline.